Inkorporasi Hermeneutika Kritis Jürgen Habermas pada Pendidikan Sejarah Bermuatan Difficult History - Ahmad, Tsabit Azinar; Mulyana, Agus; Darmawan, Wawan; Wiyanarti, Erlina (Universitas Negeri Malang, 2024)
Abstract: History education in the 21st century faces various challenges, especially in presenting sensitive and traumatic historical material, otherwise known as